Drug-induced atrial fibrillation. A narrative review of a forgotten adverse effect - Juan Tamargo; Julián Villacastín; Ricardo Caballero; Eva Delpón (Elsevier, 2024)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with an increased morbidity and mortality. There is clinical evidence that an increasing number of cardiovascular and non-cardiovascular drugs, mainly anticancer drugs, can induce AF either in patients with or without pre-existing cardiac disorders, but drug-induced AF (DIAF) has not received the attention that it might deserve. In many cases DIAF is asymptomatic and paroxysmal and patients recover sinus rhythm spontaneously, but sometimes, DIAF persists, and it is necessary to perform a cardioversion. Furthermore, DIAF is not mentioned in clinical guidelines on the treatment of AF. The risk of DIAF increases in elderly and in patients treated with polypharmacy and with risk factors and comorbidities that commonly coexist with AF. This is the case of cancer patients. Under these circumstances ascribing causality of DIAF to a given drug often represents a clinical challenge. We review the incidence, the pathophysiological mechanisms, risk factors, clinical relevance, and treatment of DIAF. Because of the limited information presently available, further research is needed to obtain a deeper insight into DIAF. Meanwhile, it is important that clinicians are aware of the problem that DIAF represents, recognize which drugs may cause DIAF, and consider the possibility that a drug may be responsible for a new-onset AF episode.